Deficient Photosystem II in Agranal Bundle Sheath Chloroplasts of C(4) Plants - Woo, K. C. (1970)
A method is described for separating mesophyll and bundle sheath chloroplasts from the leaves of C(4) plants. The agranal bundle sheath chloroplasts are inactive in the Hill reaction, whereas granal bundle sheath and granal mesophyll chloroplasts exhibit normal photosystem II activity. The agranal bundle sheath chloroplasts are deficient in photosystem II; they lack cytochrome b-559 and the fluorescence bands associated with photosystem II. All the chloroplasts exhibit photosystem I activity.